Decreasing food fussiness in children with obesity leads to greater weight loss in family‐based treatment. Issue 10 (7th September 2016) - Hayes, Jacqueline F.; Altman, Myra; Kolko, Rachel P.; Balantekin, Katherine N.; Holland, Jodi Cahill; Stein, Richard I.; Saelens, Brian E.; Welch, R. Robinson; Perri, Michael G.; Schechtman, Kenneth B.; Epstein, Leonard H.; Wilfley, Denise E.
Abstract : Objective: Food fussiness (FF), or the frequent rejection of both familiar and unfamiliar foods, is common among children and, given its link to poor diet quality, may contribute to the onset and/or maintenance of childhood obesity. This study examined child FF in association with anthropometric variables and diet in children with overweight/obesity participating in family‐based behavioral weight loss treatment (FBT). Change in FF was assessed in relation to FBT outcome, including whether change in diet quality mediated the relation between change in FF and change in child weight. Methods: Child ( N  = 170; age = 9.41 ± 1.23) height and weight were measured, and parents completed FF questionnaires and three 24‐h recalls of child diet at baseline and post‐treatment. Healthy Eating Index‐2005 scores were calculated. Results: At baseline, child FF was related to lower vegetable intake. Average child FF decreased from start to end of FBT. Greater decreases in FF were associated with greater reductions in child body mass index and improved overall diet quality. Overall, diet quality change through FBT mediated the relation between child FF change and child body mass index change. Conclusions: Children with high FF can benefit from FBT, and addressing FF may be important in childhood obesity treatment to maximize weight outcomes.